Colonoscopy decreases mortality in colorectal cancer patients compared with fecal immunochemical test. Issue 10 (3rd July 2022) - Sung, Soo‐Yoon; Choi, Hyun Ho; Kim, Sukil; Park, Bo Ram; Kim, Young Ki; Kim, Hyung‐Keun; Cho, Young‐Seok; Kim, Sang Woo; Kim, Sung Soo; Chae, Hiun‐Suk
Abstract: Background and Aim: Colonoscopy and fecal immunochemical test (FIT) are commonly used screening methods for the detection of colorectal cancer (CRC), but their effects on survival have not been compared. We compared survival outcomes in patients with CRC according to the exposure history to colonoscopy or FIT before diagnosis of CRC. Methods: We performed a nationwide population‐based retrospective cohort study using Korean national‐insurance claims data. In total, 24 875 patients with CRC diagnosed in 2012 were included. The patients were divided into three groups in terms of examinations performed during the 10 years prior to CRC diagnosis: the colonoscopy group, the FIT group, and the never‐screened group. Survival outcomes were compared among the three groups. The colonoscopy group and FIT group were matched using propensity score‐matching method. Results: The cohort consisted of 9619 patients in the colonoscopy group, 6936 patients in the FIT group, and 8320 patients in the never‐screened group. The 5‐year overall survival rates were 74.1% in the colonoscopy group, 65.9% in the FIT group, and 59.6% in the never‐screened group ( P < 0.001). The adjusted hazard ratios for death were 0.56 (95% confidence interval [CI], 0.53–0.59) in the colonoscopy group and 0.78 (95% CI, 0.74–0.82) in the FIT group compared with the never‐screened group. In the matched cohort, the adjusted hazard ratios for death was 0.76 (95% CI, 0.72–0.81) in the colonoscopy group compared with the FIT group. Conclusion: Colonoscopy is a more effective method for reducing mortality in patients with CRC compared with FIT.